The functional roles of competitive endogenous RNA (ceRNA) networks in apoptosis in human cancers: The circRNA/miRNA/mRNA regulatory axis and cell signaling pathways - Mina Shahpari; MohamadReza Hashemi; Tayebeh Younesirad; Aida Hasanzadeh; Mohammad mahdi Mosanne; Mohamadreza Ahmadifard (Heliyon)
Circular RNAs are noncoding RNAs with circular conformation mainly due to backsplicing event. CircRNAs can potentially impact cell biological processes by interacting with cell signaling pathways. Numerous circRNAs have been found to be aberrantly expressed in a variety of cancers. These RNAs can act as ceRNA (competitive endogenous RNA) by sponging certain miRNAs to form circRNA/miRNA/mRNA networks. Dysregulation of ceRNA networks may lead to dysfunctions in various cell pathways, which modulate apoptosis-associated genes and ultimately result in cancer progression.Since disruption of apoptosis is one of the leading causes of cancer development, one approach for cancer treatment is to drive cells toward apoptosis.In this review, we present a summary of studies on the role of ceRNA networks in cellular signaling pathways that regulate apoptosis; these networks are suggested to be potential biomarkers for cancer treatment.